การประเมินโครงการสถานศึกษาปลอดภัย ของโรงเรียนอนุบาลสวี (บ้านนาโพธิ์) สำนักงานเขตพื้นที่การศึกษาประถมศึกษาชุมพร เขต 2 - Muenthong, Waikun (Journal of MCU Nakhondhat, 2022)
The objectives of this research paper were to 1) assess the environment of the Safe School Project of Sawi Kindergarten School. (Ban Na Pho) 2) Evaluate the preliminary factors of the Safety School Project Sawee Kindergarten (Ban Na Pho) 3) Evaluate the process of the School Safety Project Sawee Kindergarten (Ban Na Pho) and 4) Evaluate the productivity of the Safe School Project of Sawi Kindergarten School. (Ban Na Pho) The research model is survey research and experimental research. The assessment uses the CIPP Model. The target groups in the project assessment are 40 school administrators and teachers, 10 basic school committees, 700 Kindergarten 2 – 6th-grade students, and parents of kindergarten students. 2 – Grade 6 of 350 students. The assessment tools were the Safety Education Project Assessment Form of Sawi Kindergarten School (Ban Na Pho), totaling 10 pieces. The statistics used in the data analysis were percentage, mean, and section. standard deviation The results of the assessment showed that 1) the assessment of the environment of the safety education project 2) The preliminary assessment of the safety school project 3) Assessing the process of the safety school project 4) the Assessment of the safety education project The successive results can be separated as follows. 4.2 Assessing the satisfaction of school administrators and teachers with the safety school project It was at the highest level. At a high level. 4.4 Assessment of student’s satisfaction with the safety school project at a high level